Efektivitas Penerapan Media E-Learning Berbasis Open Source Terhadap Kemampuan Problem Solving Matematis Siswa MTs Di Kabupaten Tangerang - Rina Hidayati Pratiwi; Riesto Atantio Fajri; Hasbullah (Postgraduate, University of Mataram, 2025)
Technology-based learning media is an important tool in supporting interactive and adaptive learning processes in the digital era. This study aims to evaluate the effectiveness of open source-based e-learning media